Physiology Sport Approaches: The Role of Walking in Dopamine Stimulation for Transforming Habits and Mental Health - Zulkarnain Zulkarnain; Asnaini Asnaini; Rini Fitria; Uswatun Hasanah (CV. FOUNDAE, 2024)
This study investigates the connection between dopamine stimulation, negative habit management, and mental health improvements through walking. Dopamine, a key neurotransmitter in the brain's reward system, plays a crucial role in motivation, self-control, and emotional regulation. This study aims to evaluate whether walking, as a form of altruistic behavior and social commitment, can stimulate dopamine release that promotes positive emotions, better self-regulation, and the reduction of negative habits. This descriptive quantitative study involved 250 respondents aged 20–50 who regularly walked 3 to 5 times per week. This study measured mental health parameters, including stress, anxiety, and depression, as well as negative habits, including overthinking and poor sleep patterns. The findings demonstrated significant improvements, including reductions in stress (-58%), anxiety (-53%), and depression (-54%), along with increases in happiness (+24%) and calmness (+20%). Behavioral changes were also observed, such as decreased overthinking (-45%) and poor sleep patterns (-46%), alongside enhancements in positive thinking (+27%), social awareness (+28%), and optimism (+29%). These changes suggest an increase in dopamine production associated with regular walking activities. This study highlights that walking is an accessible physical intervention that can enhance psychological well-being, reduce destructive behaviors, and strengthen dopamine-related neurobiological pathways. Additionally, this study contributes to positive psychology and exercise science by providing insights into the role of walking in supporting mental health and building personal resilience.